Perspective goes up time in Hannah Arendt and Koselleck: two readings on the break between the Present and the Past - Barros José D'Assunção (Argumentos - Revista de Filosofia, 2014)
This article aims, on a perspective of comparative historiography, to develop an analysis of the recent reflections about contemporaries sensations of rupture between Present and Past, examining in particular the thought of two authors – Reinhart Koselleck and Hannah Arendt – about the relations between Present, Past and Future. The initial point of the analysis referees to the essay Future Past, written by Koselleck – an essay in witch one this historian develop his principal considerations about the three instances of temporality, using the concepts of “experience space” and “expectative horizon”. In the sequence, it is made a comparison between the position of Koselleck and the thought of Hannah Arendt around these questions, developed by this philosopher on basis in an insight of Franz Kafka.